2021
DOI: 10.1002/jso.26660
|View full text |Cite
|
Sign up to set email alerts
|

Joint‐sparing versus nonjoint‐sparing reconstruction of the radius following oncologic resection: A systematic review

Abstract: Background and Objectives: Reconstructions of the distal radius are uncommon procedures. This systematic review compares joints-sparing (JS) versus nonjointsparing (NJS) reconstructions following oncologic resection of the distal radius.Methods: A search was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Collected outcomes included patient-reported outcome measures (PROMs), range of motion and grip strength, and complication and reoperation rates.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…There have been conflicting results when examining patient function following surgical treatment of GCTs of the distal radius, with series showing no difference in functional outcome scores between joint preserving procedures compared to joint resection. 9,16 However in a recent series by Abuhejleh et al, 19 the authors noted improved functional outcomes with joint salvage. In the current study, we found no difference in patient outcome when comparing all patients undergoing joint salvage or joint preservation, however, we noted a difference when examining qDASH when comparing patients undergoing an arthrodesis and those that did not.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…There have been conflicting results when examining patient function following surgical treatment of GCTs of the distal radius, with series showing no difference in functional outcome scores between joint preserving procedures compared to joint resection. 9,16 However in a recent series by Abuhejleh et al, 19 the authors noted improved functional outcomes with joint salvage. In the current study, we found no difference in patient outcome when comparing all patients undergoing joint salvage or joint preservation, however, we noted a difference when examining qDASH when comparing patients undergoing an arthrodesis and those that did not.…”
Section: Discussionmentioning
confidence: 97%
“…There have been conflicting results when examining patient function following surgical treatment of GCTs of the distal radius, with series showing no difference in functional outcome scores between joint preserving procedures compared to joint resection 9,16 . However in a recent series by Abuhejleh et al, 19 the authors noted improved functional outcomes with joint salvage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations